Pencegahan Penggelapan Pajak Melalui Peningkatan Religiusitas, Penanggulangan Machiavellianism Dan Transformasi Digital : Studi Berdasarkan Perspektif Gender - Nataliawati, Rita; Sulistyowati, Rina; Prananda , Azhira; Afifah, Ulul (Owner : Riset dan Jurnal Akuntansi, 2024)
Lack of awareness of taxpayers and an attitude that does not care about the importance of the role of taxes can give rise to attitudes of tax avoidance which can enable fraudulent practices to occur in the tax system. In practice, the revenue obtained by the state from taxes is often irregular or diverted by irresponsible individuals, one of which is tax evasion. This research tests whether Religiosity, Overcoming Machiavellianism and Digital Transformation have an effect on tax evasion which is moderated by gender. The author uses a positive accounting approach which is built on assumptions and social reality including human behavior. This research is a quantitative research that uses primary data obtained through distributing questionnaires in the form of questions for the variables religiosity, digital transformation Machiavellianism using a Likert scale and tax evasion. Gender variable uses a dummy. The population of this study was 80 employees of KPP Pratama Lamongan. Sample selection was carried out using a purposive sampling technique, namely selecting samples based on criteria. Data analysis in this study used the structural equation modeling partial least squares (SEM-PLS) technique as an alternative method for the covariance based structural equation model (CB-SEM), with the help of the WarpPLS version 3.0 application. The research results obtained are that religiosity and digital transformation have an effect, Machiavellianism has no effect on tax evasion, Gender moderates the effect of increasing Religiosity and Overcoming Machiavellianism and Gender does not moderate Digital Transformation on preventing tax evasion